(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article focuses on the translation aspects of the globalization of political discourse, a new phenomenon that linguistic science has not given much attention to. The growing interdependence and relationship between nations and peoples, as well as the need for their cooperation to solve global problems, require that representatives of all nations, peoples, and cultures, as well as all Earth civilizations, be involved in the political discourse. Additionally, modern global means of communication, which have successfully overcome borders and created global communication spaces, provide a technical support for the global political discourse